The Relationship Between Family Conditions and Job Satisfaction of Tax Auditors at the Primary Tax Office in Pangkalan Kerinci - Oktavia Oktavia; Syafiq Marzuqi; Gunarti Gunarti; Tatianningsih Tatianningsih; Binar Ariamukti (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
This study investigates the relationship between personal family conditions and job satisfaction, as family conditions are a significant factor influencing employee productivity and work-life balance. The research focuses on tax auditors at the Primary Tax Office in Pangkalan Kerinci, who exhibit diverse demographic profiles, including age, family status, and number of children. Using the Minnesota Satisfaction Questionnaire (MSQ-13), the study examines four dimensions of job satisfaction: work environment, work-life balance, social relationships, and job achievement. Employing a quantitative survey method, the study sampled all 10 tax auditors through total sampling. Data analysis included validity and reliability testing and correlation analysis. The findings revealed that the MSQ-13 instrument is valid and reliable, with a Cronbach's Alpha of 0.812. Work environment, work-life balance, and positive social relationships significantly influence job satisfaction, while employees separated from their families face challenges in maintaining work-life balance. Positive workplace relationships enhance satisfaction, but conflicts within teams reduce motivation. Ultimately, a supportive work environment, balanced work-life conditions, and strong social relationships are key factors driving job satisfaction and productivit.